(untitled) (Global Journal of Medical Research, 2021)
Neuropsychological Rehabilitation (NR) is understood as a process of using a wide variety of strategies deliberately centered on one person, which should stimulate his/her development, or the use of available resources to obtain a good occupational performance. Concerning this point, the intervention must be understood broadly, considering people in their contexts, activities and relationships. In order to attend these principles, the key element for success in proposing an NR plan is the active use, by the rehabilitator, of a clinical formulation process (CF). Considering the infinity of possible influences on an individual’s overall level of functioning, the formulation of factors is extremely useful to guide all the people involved, from the clinical team to the patient’s family, in order to understand the current problems faced by the person, to delineate the intervention and to prospect for future steps.